Thoracic surgeons’ practice and attitude towards surgical antimicrobial prophylaxis in VATS lung surgery: A survey within a large medical consortium - Xiaotong Gu; Yue Liu; Yanguo Liu; Jing Huang; Yi Liu; Lin Huang; Xiaohong Zhang; Rongrong Fan (PLoS ONE, 2026)
Background and objectives Surgical site infections (SSIs) are a significant post-surgery complication, impacting mortality, morbidity, and healthcare costs. Surgical antimicrobial prophylaxis (SAP) is pivotal in SSIs prevention. This study aimed to evaluate the current use of SAP in video-assisted thoracoscopic surgery (VATS) lung surgery in China. Methods A descriptive, cross-sectional survey study was conducted among thoracic surgeons within a large medical consortium in order to assess their practice and attitude about SAP. A three-section multiple-choice online questionnaire was designed and distributed via WeChat software to thoracic surgeons. The surgeons’ answers were considered consistent when they were in accordance to clinical guidelines. Results 89 thoracic surgeons were requested to participate in this study and their response rate was 73.03%. Preoperatively, 60.00% administered antimicrobials, predominantly within 0.5 to 1 hour before surgery, with cefuroxime as the preferred agent. Intraoperatively, 32.31% did not administer additional antimicrobials, and postoperatively, 90.77% prescribed them, often continuing until drainage tube removal. Surgeons frequently upgraded prophylaxis, especially postoperatively. Deviations from guidelines were common, particularly in postoperative SAP duration (76.92%), intraoperative redosing decisions (58.33%), and preoperative SAP administration (40.00%). Departmental habits significantly influenced SAP practices. The primary reason for inconsistencies was the absence of patient-specific considerations in the guidelines, affecting nearly half of the cases. Experienced surgeons were more likely to cite this lack of patient-specific attention as a reason for deviation. Conclusion The study underscores the need for updated, multidisciplinary guidelines for VATS lung surgery, emphasizing the importance of a collaborative approach among healthcare professionals to optimize individualized SAP.